2016
DOI: 10.1519/jsc.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Marathon Time Using Exhaustive Graded Exercise Test in Marathon Runners

Abstract: The study aimed to investigate the correlation between time on a treadmill test and exhaustion 2 weeks before a road marathon and the subsequent road marathon performance time (MPT). The study recruited 59 runners entered in the Melbourne 2012 marathon, Canberra 2013 marathon, and Gold Coast 2013 marathon. Forty runners completed both the graded exercise treadmill test to exhaustion and the 42.2 km marathon. Nineteen participants dropped out of the study due to illness, injury, or did not begin the treadmill t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…For both of these studies, years running were not associated with ultra-marathon race time. Also, years running were not associated with marathon time for male marathoners [29]. Years running would seem to be more important for shorter runs, and maybe this would have to do with the intensity of training for performance in shorter runs, relying on less volume but more intense training, which would be easier for a non-novice runner.…”
Section: Discussionmentioning
confidence: 99%
“…For both of these studies, years running were not associated with ultra-marathon race time. Also, years running were not associated with marathon time for male marathoners [29]. Years running would seem to be more important for shorter runs, and maybe this would have to do with the intensity of training for performance in shorter runs, relying on less volume but more intense training, which would be easier for a non-novice runner.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increased popularity of marathon running, a large number of studies have examined determinants of race time [1][2][3][4]. Nowadays, it is well known that marathon race time might be predicted by performance indices (e.g., 10 km race time, number of previously finished marathon races) [2], training volume and intensity [1,3], and physiological [5] and anthropometric characteristics (e.g., body mass index) [4]. In addition, marathon race time has been related to body composition [6], where a higher body fat (BF) percentage was associated with slower race time.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that half of the variance in pacing was accounted for by the variance in race time ( Haney and Mercer, 2011 ). In turn, race time could be predicted by aerobic capacity ( Till et al, 2016 ; Salinero et al, 2017 ). As shown in the present study, aerobic capacity was related inversely with variation in pacing in men, i.e., the higher the aerobic capacity the less variable the pacing.…”
Section: Discussionmentioning
confidence: 99%